Kajian Ergonomi di Sentra Persiapan BCCT: Menggugah Minat Baca-Tulis Anak Usia Dini Melalui Penataan Lingkungan Belajar yang Ergonomis - Laily Hidayati (Universitas Al-Hikmah Indonesia, 2018)
Humans influence and are influenced by their environment. That rule is fully accepted in the study of behavioral science or psychology. Thoughts, feelings, behaviors, and tendencies to act can